2022
DOI: 10.1186/s13018-022-03147-9
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic analysis of 8000 acute vertebral fractures: evolution of treatment and complications at 10-year follow-up

Abstract: Study design This is a retrospective cohort study. Objectives This study aims to determine the proportional incidence, clinical characteristics, treatment patterns with complications and changes in treatment of vertebral fractures over 10 years at a Swiss university hospital. Methods A retrospective cohort study was performed. All patients with an acute vertebral fracture were included in this study. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 33 publications
1
27
1
Order By: Relevance
“…The majority of complications were nonsurgical and not life threatening and could thus be treated conservatively. Overall, the number of complications was comparable to or even lower than that reported in the literature [30,31].…”
Section: Discussionsupporting
confidence: 77%
“…The majority of complications were nonsurgical and not life threatening and could thus be treated conservatively. Overall, the number of complications was comparable to or even lower than that reported in the literature [30,31].…”
Section: Discussionsupporting
confidence: 77%
“…Author details 1 Emergency Department, Sonnenhof Hospital, Bern, Switzerland. 2 Department of Anesthesiology, Spitalregion Rheintal, Werdenberg, Sarganserland, Grabs, Switzerland.…”
Section: Authors' Contributionsmentioning
confidence: 99%
“…With great interest we read the retrospective cohort study by Bigdon et al entitled “Epidemiologic analysis of 8000 acute vertebral fractures: evolution of treatment and complications at 10-year follow-up” [ 1 ]. The authors are to be congratulated on the extensive work they performed leading up to this large study.…”
mentioning
confidence: 99%
“…We have studied the article by Bigdon et al, published recently in the Journal of Orthopaedic Surgery and Research, with great interest [1]. The authors analysed n = 330,225 emergency room patients and identified more than 8000 vertebral fractures in 4772 patients over a 10-year period.…”
Section: Dear Editormentioning
confidence: 99%